The impacts of institutional characteristics on capital structure: Evidence from listed commercial banks in China - Phassawan Suntraruk (2018)
© 2017 Inderscience Enterprises Ltd. In China, bank capital structure is subject to the minimum capital requirements regulated by the Basel Accords. Nonetheless, with the rapid development of the Chinese banking sector, institutional characteristics have an impact on how banks finance their operations and growth. Therefore, the purpose of this study is to explore the institutional factors that influence the capital structure of listed commercial banks in China. Using unbalanced panel data of 25 listed Chinese commercial banks during the period of 2003 to 2015, the results indicate that Chinese listed commercial banks with more profitability or those having a low percentage of shares owned by the largest shareholders are less likely to employ debt financing. Moreover, this study shows that the size of Chinese listed commercial banks increases with debts. The results of this study will assist managers of listed commercial banks to create adequate capital structure decision-making to further maximise bank value. In addition, both investors and depositors will be able to judge how safe the bank capital is, after understanding the determinants of capital structure, which will help in reducing their risk exposure.